Revision Anterior Cruciate Ligament Reconstruction and Increased Tibial Slope: When to Perform a Slope-Altering High Tibial Osteotomy - Gian Andrea Lucidi MD; Bálint Zsidai MD; Philipp W. Winkler MD; Brian M. Godshaw MD; Jonathan D. Hughes MD; Volker Musahl MD (SAGE Publishing, 2022)
Background: Slope-correcting high tibial osteotomy (HTO) is gaining popularity for mitigating the impact of posterior tibial slope (PTS) on graft failure in patients requiring revision anterior cruciate ligament (ACL) reconstruction surgery. Biomechanical and clinical studies have demonstrated that PTS reduction results in decreased graft forces and satisfactory patient outcomes, making it an important technique in the setting of complex revision ACL reconstruction (ACL-R). Indications: Slope-correcting HTO can be performed for the management of recurrent knee instability after ACL-R due to a high PTS of 12° or greater. Technique Description: A 3- to 4-inch incision is made along the tibia using an anteromedial approach, and the exposed patellar tendon is protected using a retractor. The anterior compartment is exposed by an incision in the tibialis anterior fascia, followed by elevation of the tibialis anterior and placement of a Hohmann retractor. Subperiosteal elevation of the medial collateral ligament (MCL) is performed on the medial side of the tibial tubercle. The position of eventual screw fixation is marked, and a straight tubercle osteotomy is performed without anteriorization, leaving a freely exposed proximal tibia. Two K-wires are used to mark the location of the osteotomy. Soft tissue structures are protected with Hohmann retractors on both sides while using an oscillating saw to perform the osteotomy. A few degrees (1°-3°) of overcorrection are preferred. The osteotomy is completed, retaining 1cm of posterior hinge. The wedge is removed and reduced by hyperextending the knee under gentle manual traction. Pre-contoured, low-profile plates with locking screws are placed, with 3 screws proximally and another 3 distally. During concurrent ACL-R, the screws should leave room for drilling of the ACL tibial tunnel. Results: Studies investigating the effects of slope-correcting HTO concurrent to revision ACL-R have reported reduced anterior tibial translation and rotatory knee instability, improved patient-reported outcomes, and a reduction in graft failure risk. Description/Conclusion: Slope-reducing HTO is an essential technique in the arsenal of complex ACL surgeons aiming to correct the detrimental effect of an increased PTS on ACL graft integrity in the setting of revision ACL-R.